A Young Male Presenting with Polyuria and Unilateral Exophthalmos - Das, Aparna; Cader, F Aaysha (Journal of Bangladesh College of Physicians and Surgeons, 2015)
Abstract not available J Bangladesh Coll Phys Surg 2014; 32: 241-243